FATWA MUI TENTANG ATRIBUT KEAGAMAAN DALAM PERSPEKTIF KOMUNIKASI DAKWAH - Muhd. Maryadi Adha (al-Balagh : Jurnal Dakwah dan Komunikasi, 2018)
Fatwa of MUI Number 56 in 2016 concerning about â€œReligious Attributes of Non-Muslimsâ€ issued as guideline for Indonesian Muslims addressing the phenomenon of using non-muslim religious attributes, while promoting good relations between Muslims and other religious people. The purpose of this study is to analyze how the MUI fatwa efforts to maintain the harmony between religious communities and the harmonious life in society, nation, and state. Using qualitative research methods in communication of da'wah perspective, this study focuses direct attention into 3 (three) things thatâ€™re: 1) analysing about some keywords contained in the fatwa; 2) understanding the quality of fatwa messages; and 3) analysing the implications of fatwa in Indonesian religious life. Generally, in communication of da'wah perspective, the fatwa still raises multi-interpretations, particularly among the communicants, especially on keywords in the fatwa which have an impact on the tension of religious relations in Indonesia, though not too significant.